Analysis of Bean (Phaseolus vulgaris) Growth Due to Treatment of Vermicompost and Different Types of Mulch - Ahmad Raksun; Mohammad Liwa Ilhamdi; I Wayan Merta; I Gde Mertha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Beans are vegetables that are widely cultivated in Indonesia. The growth of beans is determined by internal and external factors. The external factor that affects the growth of beans is the availability of nutrients. Vermicompost is an organic fertilizer that can be used to increase beans growth. Research has been carried out on Analysis of Bean (Phaseolus vulgaris) Growth Due to Treatment of Vermicompost and Different Types of Mulch. This study aims to determine: (1) the effect of the type of mulch on the growth of beans, (2) the effect of different doses of vermicompost on the growth of beans, (3) the effect of the combination of different types of mulch and the dose of vermicompost on the growth of beans. In this study, a 2-factor design with 4 replications was used. Bean growth parameters include number of leaves, leaf length, leaf width and plant height. Data were analyzed by Anova. The results of the study were: (1) the application of vermicompost significantly increased the number of leaves and plant height, but could not increase the length and width of the beans leaves. (2) the use of mulch can increase the number of leaves, stem height, number of leaves and leaf width of beans, black silver plastic mulch gives better results than rice straw mulch, (3) the interaction of mulch type and dose of vermicompost has no significant effect on all growth parameters measured.